PHILOSOPHICAL ANALYSIS OF THE ESSENCE OF AESTHETIC EDUCATION (Scientific journal of the Fergana State University, 2024)
The article philosophically analyzes aesthetic education, which is an important part of socio-spiritual life in all periods, its place and role in human development, the views of mature thinkers of their time on aesthetic education and its importance, the essence and purpose of aesthetic education.